When Barthes meets Ben: Barthesian semiologies in selected short stories of Bienvenido N. Santos (BNS) - Macatangay, Jose Clarete (Penerbit Universiti Kebangsaan Malaysia, 2024)
In literary criticism, the semiotics of Roland Barthes, a widely used approach in popular culture, is rarely applied to short stories, particularly in Philippine diaspora literature, as evident in the dearth of studies conducted in the field. To fill this gap, this study aims to unveil the ideological underpinnings in Bienvenido N. Santos’s (BNS) four selected short stories by conducting a two-level semiotic analysis of their representation of Filipino-American experiences of exile. For the first level of analysis, the short stories' intrinsic elements, such as images, characters, characterization, setting, figures of speech, and dialogues, were examined to demystify the signifier-signified relationship. For the second level of analysis, the ideological functions behind the myths were discussed. The Filipino-American exile is a Filipino with a sense of pride in fulfilling the American Dream, a pursuit of a better life, and who aspires for financial stability, social mobility, and greater opportunities for one’s self and family. In realizing this American Dream, there is a hegemonic group that imposes its norms on the citizens of one of its former colonies. This study, anchored on Barthes’s semiologies, proves that literature, like popular culture artefacts, may entrench colonial beliefs instead of playing the ideal role in decolonial resistance if not closely read. Future researchers may apply the Barthesian framework to Philippine literary texts, other BNS’s anthologies, other authors, and 21st-century diaspora literature.